PENENTU KINERJA KEUANGAN SERTA KONSEKUENSINYA TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR (Students' Journal of Economic and Management, 2013)
The main objective of this study was to examine the impact of these factors on financial performance of manufacture industry that listed at Indonesia Stock Exchange over 2009-2011. The objective of this research is to test and analyze whether debt equity ratio, current ratio, institutional ownership, firm size to financial performance and to analys the influence of financial performance to firm value. Thirty-five companies met the criteria and were analyzed descriptive statistic and multiple regression were performed to test the hypothesis. Hypothesis testing is based on balancing theory, information theory asimetric, packing order theory, signaling theory, agency theory and previous empirical evidence. The conclusion shows that the debt equity ratio and firm size are influence financial performance, but current ratio and institutional ownership are not significant impact of financial performance. The other conclusion show that financial performance influence firm value.   Keyword : debt to equity ratio, current ratio, institusional ownership, firm size, return on asset, firm value